2003
DOI: 10.1038/sj.npp.1300254
|View full text |Cite
|
Sign up to set email alerts
|

The Pineal Gland is Critical for Circadian Period1 Expression in the Striatum and for Circadian Cocaine Sensitization in Mice

Abstract: Sensitization to psychostimulants can be influenced by circadian rhythms. The pineal gland, the main source of circadian melatonin synthesis, may influence behavioral sensitization to cocaine; mice with normal melatonin rhythms do not get sensitized at night. Clock genes such as Period1 (Per1) show rhythmic region-and strain-dependent expression in the mouse brain, and mice mutant for the Per1 gene lack cocaine sensitization. Here, for the first time we show circadian changes of PER1 protein levels in the mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
106
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 33 publications
6
106
1
Order By: Relevance
“…It has been hypothesized that it is through these "non-clock" functions that these circadian genes interact with systems involved in the development of cocaine addiction (Manev and Uz 2006;Uz et al 2003;Yuferov et al 2005b). For example, it has been reported that stimulant drug treatment produces gene expression changes in Per gene expression in the striatum without affecting the rhythmic expression in SCN (Manev and Uz 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that it is through these "non-clock" functions that these circadian genes interact with systems involved in the development of cocaine addiction (Manev and Uz 2006;Uz et al 2003;Yuferov et al 2005b). For example, it has been reported that stimulant drug treatment produces gene expression changes in Per gene expression in the striatum without affecting the rhythmic expression in SCN (Manev and Uz 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the pineal hormone melatonin modulates the rhythm of the clock gene Per1 in the pituitary gland, striatum, and adrenal cortex (15)(16)(17). Furthermore, adrenal glucocorticoids induce Per1 expression in peripheral tissues such as the liver (18,19) and modulate the rhythm of expression of the clock protein, PER2, in the oval nucleus of the bed nucleus of the stria terminal (BNST-OV) and central nucleus of the amygdala (CEA) (12,13).…”
mentioning
confidence: 99%
“…Results suggest that MEL treatment or PG prevent agerelated thymus involution through regulation of thymocyte apoptosis which, in turn, occurs through modulation of the pituitary-adrenal axis and zinc turnover determined by the pineal hormone 231 . Studies have found melatonin useful in cocaine abuse 232 , seasonal affective disorder 233,234 , delirium 235 , headache 236,237 , gallstone 238,239 , and amyotrophic lateral sclerosis 240 . Few studies have suggested melatonin as an effective radioprotective agent [241][242][243][244][245] .…”
Section: Miscellaneousmentioning
confidence: 99%